Intestinal Microbiota-Associated Metabolites: Crucial Factors in the Effectiveness of Herbal Medicines and Diet Therapies - Wang, Yiliang; Qin, Shurong; Jia, Jiaoyan; Huang, Lianzhou; Li, Feng; Jin, Fujun; Ren, Zhe; Wang, Yifei (Frontiers in Physiology, 2019)
Although the efficacy of herbal medicines (HMs) and traditional Chinese medicines (TCMs) in human diseases has long been recognized, their development has been hindered in part by a lack of a comprehensive understanding of their mechanisms of actions. Indeed, most of the compounds extracted from HMs, can be metabolized into specific molecules by the host microbiota and affect the pharmacokinetics and toxicity. Moreover, HMs modulate the constitution of host intestinal microbiota to maintain healthy gut ecology. Dietary interventions also show a great efficacy in treating some refractory diseases, among which the commensal microbiota potentially has significant implications for their high inter-individual differences. Herein, we mainly discuss the contribution of the intestinal microbiota to high inter-individual differences in response to HMs and TCMs, especially the already known metabolites of the HMs produced by the intestinal microbiota. The contribution of commensal microbiota in the inter-individual differences of dietary therapy was also briefly discussed. This review highlights the significance of intestinal microbiota-associated metabolites on the efficiency of HMs and dietary interventions. Our review may help further identify the mechanisms of the inter-individual differences of HMs and dietary interventions from the perspective of their interactions with intestinal microbiota.